Penerapan Algoritma Profile Matching pada Aplikasi Computer Based Test (CBT) dalam Proses Seleksi Mahasiswa Baru - Lusi Robiatul Fadilah; Rianto Rianto; Rahmi Nur Shofa (Teknik Informatika Universitas Pamulang, 2021)
Computer Based Test (CBT) is a test that is administered using a computer as tools or the main medium in conducting tests or exams. However, not all universities have utilized this technology. One of them is the Sekolah Tinggi Ilmu Kesehatan (STIKes) Kuningan, which has not yet used a computerized system. Examination implementation and manual processing of exam scores are an obstacle in the selection process for new students. With the existence of a Computer Based Test (CBT) application, it is hoped that it can facilitate the implementation of the test. However, the use of Computer Based Test (CBT) technology is not sufficient in determining which participants get the best score. The Profile Matching algorithm is chosen as an algorithm that can assist in decision making. There are 5 criteria used, that is the value of CBT and parents' income as criteria for the type of Core Factor, Mathematics National Exam scores, English National Exam scores, and Indonesian Language National Exam scores as criteria for the type of Secondary Factor. Testing is done by comparing the results of calculations on the system and Microsoft Excel calculations where there are 3 different values of the Core Factor and Secondary Factor. There is a discrepancy in the test results when multiple profiles have the same final value. One of them, Dea Nur Alifah and Rahma Nurlita with CF values of 60%, SF 40% and CF 70%, SF 30% has a final value of 5.78, is in the order of 3 and 4. Furthermore, the CF values of 80% and SF 20% are both has decreased in value, to 5.77 and still ranks 3 and 4. The application of the Profile Matching algorithm with an output in the form of ranking values in the Computer Based Test (CBT) application is still not optimal.